HDAC6 promotes inflammation in lupus nephritis mice by regulating transcription factors MAFF and KLF5 in renal fibrosis - Meihui Deng; Xiao Tan; Xiaojie Peng; Weimin Zheng; Rui Fu; Shanshan Tao (Renal Failure)
Aim This study explored the effect and mechanism of MAFF and HDAC6 on renal fibrosis and inflammation in lupus nephritis (LN).Methods IL-33 treated renal epithelial cells and MRL/lpr mice were respectively used for in vitro and in vivo experiments. The expressions of HDAC6, MAFF, and KLF5 were measured in cells and renal tissues. Before and after cell transfection, the morphological changes in renal tissues were observed using Hematoxylin and eosin (H&E) and Masson staining. The proteinuria, serum creatinine (SCr), blood urea nitrogen (BUN), and double-stranded DNA (dsDNA) levels were detected by biochemical analysis. The expressions of fibrosis and inflammation related proteins (including α-SMA, Vimentin, IL-1β, IL-6, and TNF-α), p65, and iNOS were also detected. The relationship among MAFF, HDAC6, and KLF5 was determined by chromatin immunoprecipitation and dual luciferase reporter gene assay.Results Renal tissues and cell models had elevated expressions of HDAC6 and KLF5, and decreased MAFF expression. HDAC6 suppression or MAFF overexpression led to suppression of proteinuria, SCr, BUN, and dsDNA levels, as well as attenuation of inflammatory infiltration and collagen deposition. HDAC6 can suppress MAFF expression via deacetylation to abolish its suppression of KLF5 expression, thus increasing KLF5 expression. In vivo and in vitro experiments showed the suppressive effect of HDAC6 suppression on renal fibrosis and inflammation can be abolished by KLF5 overexpression.Conclusion HDAC6 suppresses MAFF expression via deacetylation to elevate KLF5 expression, which consequently enhances fibrosis and inflammatory response in LN.